Road to EU - Enlargement and Competitiveness of Western Balkan Companies - Zlatan Fröhlich (European Regional Science Association (ERSA), 2005)
Non-tariff barriers limit trade within South East Europe, and many Western Balkan companies fear a negative impact of the recent EU enlargement. At the same time, companies in the Western Balkans can reap the benefits of further integration, provided they are better informed about relevant legislation. This is a key finding that will be discussed in the paper, based on Eurochambers survey. Survey has covered Albania, Bosnia and Herzegovina, Croatia, FYR of Macedonia and Serbia and Montenegro. Special emphasis in the paper will be focused to the Croatian companies, due to the fact that is only Croatia official candidate country for EU from the Western Balkan region. According to the survey, Western Balkan companies need to catch up with their knowledge on regulatory requirements in the EU in order to fully realize the potential of the market. Despite the fact that the Union is a major export destination and companies are interested to intensify business relations, 28% have no information on EU legislation at all. The companies in the region are very much concerned about the negative impact that the recent enlargement of the EU may have on their business prospects but they feel fairly optimistic about the benefits of their own countries' membership in the EU. 69% of respondents expect easier access to the EU markets. The survey also showed that Western Balkan companies trying to do business with their south-east European neighbors or with the EU Member States suffer from bureaucratic customs procedures and lack of mutually recognized certification bodies. Every second company, on average, said that very few of their employees are able to work in a foreign language and that they have only one e-mail account for the company. However, companies in the Western Balkans do appreciate the importance of training their staff in a variety of skills and of investing into internationally recognized quality certification.
Keywords: 330